2010
DOI: 10.1093/eurheartj/ehq324
|View full text |Cite
|
Sign up to set email alerts
|

Impaired microcirculation predicts poor outcome of patients with acute myocardial infarction complicated by cardiogenic shock

Abstract: diminished sublingual PCD, at baseline or following treatment, is associated with development of multi-organ failure and is a predictor of poor outcome in patients with acute myocardial infarction complicated by cardiogenic shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
91
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(104 citation statements)
references
References 43 publications
4
91
0
2
Order By: Relevance
“…Both values incorporate the density of the vascular network as well as its perfusion status. Both have prognostic relevance (13,24) and allow the monitoring of changes following pharmacological therapy (reviewed in Ref. 25).…”
Section: Discussionmentioning
confidence: 99%
“…Both values incorporate the density of the vascular network as well as its perfusion status. Both have prognostic relevance (13,24) and allow the monitoring of changes following pharmacological therapy (reviewed in Ref. 25).…”
Section: Discussionmentioning
confidence: 99%
“…3 Emerging evidence has also shown that impairment of tissue microcirculation is associated with 30-day mortality and temporal changes in SOFA (SepsisRelated Organ Failure Assessment) scores and may be improved with MCS. 28,29 In fact, it is now well established that CS can result in both acute and subacute derangements to the entire circulatory system, including the peripheral vasculature. Extremity and vital organ hypoperfusion remains a clinical hallmark.…”
mentioning
confidence: 99%
“…This approach is unfortunately potentially biased when alterations in microvascular perfusion alter oxygen extraction capabilities such as in sepsis [40]. Microcirculatory alterations also occur in cardiogenic shock and severe heart failure [41,42], but these have less impact on SvO2, as SvO2 is already low due to the low cardiac output. The second factor to take into account is lactate levels.…”
Section: Characterization Of the Type Of Shockmentioning
confidence: 99%